Access to Resources Shapes Sex Differences Between Caring Parents - Ratz, Tom; Kremi, Katerina; Leissle, Lyndon; Richardson, Jon; Smiseth, Per T. (Frontiers in Ecology and Evolution, 2021)
In species where both parents cooperate to care to their joint offspring, one sex often provides more care than the other. The magnitude of such sex differences often varies both between and within species and may depend on environmental conditions, such as access to resources, predation risk and interspecific competition. Here we investigated the impact of one such environmental variable – access to resources for breeding – on the magnitude of sex differences in parental care in the burying beetle Nicrophorus vespilloides. This species breeds on the carcasses of small vertebrates, which are the sole food source for parents and offspring during breeding. We manipulated access to resources by providing pairs with mouse carcasses from a broad mass range (3.65–26.15g). We then monitored subsequent effects on the duration and amount of care provided by males and females, male and female food consumption and weight change during breeding, and larval traits related to offspring performance. We found that males increased their duration of care as carcass mass increased, while females remained with the brood until it had completed its development irrespective of carcass mass. There were thus more pronounced sex differences in parental care when parents had access to fewer resources for breeding. Overall, our findings show that sex differences between caring parents vary depending on access to resources during breeding. The finding that males extended their duration of care on larger carcasses suggests that access to more resources leads to a shift towards more cooperation between caring parents.